Microbes-mediated integrated nutrient management for improved rhizo-modulation, pigeonpea productivity, and soil bio-fertility in a semi-arid agro-ecology - Gupta, Gaurendra; Dhar, Shiva; Kumar, Adarsh; Choudhary, Anil K.; Dass, Anchal; Sharma, V. K.; Shukla, Livleen; Upadhyay, P. K.; Das, Anup; Jinger, Dinesh; Rajpoot, Sudhir Kumar; Sannagoudar, Manjanagouda S.; et al. (Frontiers in Microbiology, 2022)
Excessive dependence on chemical fertilizers, ignorance to organic and microbial inputs under intensive cropping systems are the basic components of contemporary agriculture which evolves several sustainability issues such as degraded soil health and sub-optimal crop productivity. This scenario urge for integrated nutrient management approaches such as microbes mediated integrated plant nutrition for curtailing the high doses as chemical fertilizers. Rationally, experiment has been conducted in pigeon pea at ICAR-IARI, New Delhi with the aim of identifying the appropriate nutrient management technique involving microbial and organic nutrient sources for improved rhizo-modulation, crop productivity and soil bio-fertility. The randomized block designed experiment consisted nine treatments viz. Control, Recommended dose of fertilizers (RDF), RDF+ Microbial inoculants (MI), Vermicompost (VC), Farm Yard Manure (FYM), Leaf Compost (LC), VC+MI, FYM+MI and LC+MI. Rhizobium spp., Pseudomonas spp., Bacillus spp. Frateuria aurantia were used as seed inoculating microbes. The results indicated the significant response of integration following the trend VC+MI> FYM+MI> LC +MI> RDF+ MI for various plant shoot-root growth attributes and soil microbial and enzymatic properties. FYM+MI significantly improved the water-stable aggregates (22%), mean weight diameter (1.13 mm) and geometric mean diameter (0.93 mm), soil organic carbon (SOC), SOC stock and SOC sequestration. The chemical properties viz. available N, P and K were significantly improved with VC+MI. Study summarizes that FYM+MI could result into better soil physico-chemical and biological properties and shoot-root development; however; VC+MI could improve available nutrients in the soil and may enhance the growth of pigeon pea more effectively. The outcomes of the study are postulated as a viable and alternative solution for excessive chemical fertilizer based nutrient management and would also promote the microbial consortia and organic manures based agro-industries. This would add into the goal of sustainable agricultural development by producing quality crop produce, maintaining agro-biodiversity and making the soils fertile and healthy that would be a ‘gift to the society’.